Penerapan Mesin Potong Tipis Adonan Keripik Dilengkapi Spring Pusher untuk Meningkatkan Produksi pada UMKM di Desa Srigonco, Bantur, Kabupaten Malang - Mindarta, Erwin Komara; Redyarsa Dharma Bintara; Dani Irawan; Taupik Yuhana; Dwi Bayu Handayani (CV. IRA PUBLISHING, 2023)
Srigonco village chip products are well known to the wider community. In the production of chips, this is done using tools that are still considered manual, either using a knife or a makeshift chopper. This is considered less effective and efficient because it requires more energy and time. The community service implementation team from the Department of Mechanical Engineering, State University of Malang (UM), answered partners' needs by providing a solution for a thin chip dough cutting machine equipped with a spring pusher. To achieve the goal of service, the procedures taken include 1) location survey, 2) social approach, 3) product development, 4) preparation of guidelines, 5) application of science and technology/TTG through outreach activities, the introduction of tools/TTG and training; 6) follow-up through modelling and mentoring; 7) monitoring and evaluation: presentation of progress and final report, and 8) fulfilling external obligations. This tool has the benefits of 1) increasing the productivity of MSMEs so they can produce more and faster, and 2) maintaining employee safety from accidents such as accidentally being injured by a knife.